Improving soil fertility recommendations in Africa using the decision support system for agrotechnology transfer (DSSAT) - Kihara, Job (Springer Netherlands, 2012)
The book gives a detailed description of the application of DSSAT in simulating crop and soil processes within various Agro-ecological zones in Africa. The book, an output of a series of 3 workshops, provides examples of the application of DSSAT models to simulate nitrogen applications, soil and water conservation practices including effects of zai technology, phosphorus and maize productivity, generation of genetic coefficients, long-term soil fertility management technologies in the drylands, microdosing, optimization of nitrogen x germplasms x water, spatial analysis of water and nutrient use efficiencies and, tradeoff analysis. The minimum dataset requirements for DSSAT is discussed. This book arises from attempts to address the limited use of models in decision support by African agricultural (both soil scientist and agronomists) scientists.